The puzzling clinical presentation of fluoropyrimidines cardiotoxicity - Linda Cucciniello; Ettore Bidoli; Elda Viel; Maria Laura Canale; Lorenzo Gerratana; Chiara Lestuzzi (Frontiers in Cardiovascular Medicine, 2022)
The cardiotoxicity of fluoropyrimidines (FP) [5-Fluorouracil and Capecitabine] is often reported as acute cardiac ischemia with rest typical angina, signs of ischemia at electrocardiogram (ECG), and ventricular kinetics abnormalities. However, silent ischemia, effort-related toxicity, and ventricular arrhythmias (VA) have been also described. The aim of this study is to report a consecutive series of 115 patients with FP cardiotoxicity observed in a single center both within clinical prospective studies and during the clinical routine. The clinical presentation widely varied as regards symptoms, ECG abnormalities, and clinical outcomes. We report also the strategies used to prevent cardiotoxicity in a subgroup of 35 patients who continued o rechallenged FP therapy after cardiotoxicity. In nearly half of the patients, the cardiotoxicity was triggered by physical effort. Typical angina was rare: the symptoms were absent in 51% of cases and were atypical in half of the other cases. ST-segment elevation and VA were the most frequent ECG abnormality; however, ST segment depression or negative T waves were the only abnormalities in 1/3 of the cases. Troponins essays were often within the normal limits, even in presence of extensive signs of ischemia. The most effective strategy to prevent cardiotoxicity at rechallenge was reducing FP dosage and avoiding physical effort. Anti-ischemic therapies were not always effective. Raltitrexed was a safe alternative to FP. Fluoropyrimidine cardiotoxicity shows a wide variety of clinical presentations in real life, from silent ischemia to atypical symptoms, acute coronary syndrome, left ventricular dysfunction (LVD), VA, or complete atrio-ventricular block. Physical effort is the trigger of cardiotoxicity in nearly half of the cases. The recognition of cardiotoxicity cannot rely on symptoms only but requires an active screening with ECG and stress test in selected cases.